Parental Readiness in Caring for Low Birth Weight: Pediatric Nursing Intervention - Novi Indrayati; Dona Yanuar Agus Santoso (NurseLine Journal, 2021)
Background: low birth weight babies (LBW) weighing less than 2500 are babies at high risk because in general, they are smaller than normal birth weight babies and immature organ function. LBW requires special care to anticipate life-threatening emergency conditions. The care process for meeting the special needs of LBW requires the involvement of parents during the hospital and after discharge from the hospital. Nurses as educators have an important role in preparing parents to care for LBW after returning from the hospital. Purpose: This study aims to determine the effect of child nursing interventions through the education of LBW infant care with parents' readiness to care for LBW. Methods: This research is a quantitative study, using a quasi-experimental design with a pre-post-test with control. The population of this study was parents who had LBW babies in Kendal District Hospital with the sampling technique using accidental sampling, the total sample was 40 parents with LBW babies. The sample was classified into two groups, namely, 20 respondents as the intervention group and 20 respondents as the control group. Results: The results of this study indicate that there was a significant differences in parent readiness scores in caring for LBW between those who were given and not given education with a P value of 0.000, used an independent sample t-test and there was an effect of education on the readiness of parents in caring for LBW used the Chi-square test with a p value of 0.002. Conclusion: Providing education to parents with LBW is one of the implementations of pediatric nursing to prepare parents to care for LBW.